Masjid Syuhada Yogyakarta di Dalam Pemberitaan Majalah Asy-Syu-un Al-Indunisiyah - Ranti Sabariani; Yuliatin Yuliatin; Sarah Widya Astuti; Hudaidah Hudaidah; Risa Martayati (Indo Publishing, 2026)
This study examines the history, news coverage, and role of the Syuhada Mosque in Yogyakarta in the lives of Muslims as represented in the Asy-Syu'un Al-Indunisiyah magazine. The Syuhada Mosque is a historic mosque built at the beginning of Indonesian independence as a form of respect for the fighters who died in defending independence. This study aims to analyze the background to the construction of the Syuhada Mosque, how it was reported in the Asy-Syu'un Al-Indunisiyah magazine, and how the mosque is represented in Islamic and social discourse in society. This study uses a historical method with a qualitative approach. Data sources consist of primary sources in the form of articles in the Asy-Syu'un Al-Indunisiyah magazine and secondary sources in the form of books, journals, and related documents. Data collection techniques were carried out through library research and documentation. The results of the study indicate that the Syuhada Mosque not only functions as a place of worship, but also has historical value as a monument to honor the martyrs who died in the struggle for independence. The news in the Asy-Syu'un Al-Indunisiyah magazine describes this mosque as a symbol of spirituality, nationalism, and unity of the Muslim community. Furthermore, the Syuhada Mosque serves as a center for educational, preaching, and social activities, contributing to the development of religious life and strengthening social ties within the community. Thus, the Syuhada Mosque holds significant significance within the historical, religious, and social contexts of Indonesian society